Photochemical Ligand Exchange Reactions of Sodium Nitroprusside: Use of Metabisulphite Ions - R. MEHTA, MAYANK; PRAJAPATI, VIPUL; C. AMETA, SURESH (Asian Journal of Chemistry, 2010)
Sodium nitroprusside contains cyanide ligands that cannot be so easily replaced chemically. An effort has been made to substitute this ligand by another anionic ligand like metabisulphite. The rate of this photochemicaI reaction has been observed spectrophotometrically. The effect of different parameters like pH, light intensity. concentration of sodium nitroprusside and metabisulphite ligand concentration on the rate of this substitution reaction have been studied. The product has beem isolated and characterized. A tentative mechanism for this photochemical substitution reaction has been proposed.